Distribution of FoxP3+regulatoryT-cells in rat’spancreatic lymph nodes under streptozotocin-induced diabetes and metformin administration - D. A. Putilin; A. M. Kamyshnyi (Patologìâ)
Type 1 diabetes mellitus is a T-cellmediated autoimmune disease characterized by the destruction of β-cells of the pancreas. Numerous studies have demonstrated the key role of FoxP3+ regulatory T-cells in the development of type 1 diabetes.